The Role of Cognitive Bias and Emotional Drive in the Dissemination of Fake News: A Review and Prospectus - Luo, Ying (International Journal Fine Arts and Creative Innovation, 2025)
The rapid proliferation of fake news in digital societies poses significant challenges to information integrity, social trust, and democratic governance. This review examines the role of cognitive bias and emotional drive in shaping the dissemination of fake news across political, health, economic, and cultural domains. Drawing on insights from psychology, sociology, neuroscience, and communication studies, the paper highlights how biases such as confirmation bias, the availability heuristic, and the illusory truth effect interact with emotional triggers including fear, anger, and hope to amplify the virality of false information. The review also analyzes the enabling role of social media platforms and algorithmic systems in reinforcing echo chambers and accelerating misinformation spread, illustrated through case studies in elections, public health crises, and environmental debates. Empirical evidence underscores that misinformation persists due to both cognitive vulnerabilities and structural features of digital ecosystems. The implications are far-reaching: strengthening media literacy and education, crafting balanced public policies, and redesigning platform architectures are essential but complex tasks. Future research must integrate cognitive science, communication, political science, and data science, leveraging machine learning and big data for detection while also addressing the psychological and emotional drivers of misinformation. This paper argues that reducing the harmful impact of fake news requires a multi-stakeholder approach, where media users, researchers, policymakers, and technology developers work collectively to foster resilient and trustworthy information environments.